Perancangan Aplikasi Duplicate Document Scanner Menerapkan Algoritma SHA 1 - Utami, Nur Indah; Nadeak, Berto; Saputra, Imam (JURIKOM (Jurnal Riset Komputer), 2021)
We are now in the era of the digital world. Many industries have switched to digital technology such as photos, videos, music, and so on. Of course, this change brings many benefits for us in terms of speed and data access. This has an impact on the number of the same files or duplicate files stored on one computer, this is certainly not needed and takes up storage space. As with document files, it will be very difficult to distinguish document files without seeing the contents of the document file. In cryptography there is a hash function which is a one-way function that can generate the identity of a file, where if the document file contains the same content, it will produce the same hash value. This can be used to identify the same or duplicate document files. In the hash function there is the SHA-1 method or the Secure Hash Algorithm 1 which is one of the hashing algorithms that is often used to encrypt data with a width of 20 bytes or 160 bits.